1997
DOI: 10.1093/chemse/22.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Inositol-1,4,5-trisphosphate Induces Responses in Receptor Neurons in Rat Vomeronasal Sensory Slices

Abstract: Using the whole-cell mode of the patch-clamp technique, we recorded action potentials, voltage-activated cationic currents and putative second messenger-activated currents in receptor neurons in the vomeronasal sensory epithelium of female rats. The resting membrane potential and input resistance were -45.5 +/- 2.5 mV (mean +/- SEM, n = 39) and 1.5 +/- 0.2 G omega (mean +/- SEM, n = 37). Current injection of 1-3 pA induced overshooting action potentials. The firing frequency increased with increasing current i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
44
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…Our results suggest that MHC class I peptides stimulate the female VNO via the production of Ins(1,4,5)P 3 . This result complements other studies that show Ins(1,4,5)P 3 levels increase in the VNO membrane preparations during stimulation with urinary pheromones (Sasaki et al, 1999;Kroner et al, 1996;Wekesa and Anholt, 1997;Wekesa et al, 2003;Inamura et al, 1997a;Inamura et al, 1997b). The role of Ins(1,4,5)P 3 in the production of calcium and generation of an action potential is still uncertain along with the role of calcium once it has entered the cell.…”
Section: Discussionsupporting
confidence: 85%
“…Our results suggest that MHC class I peptides stimulate the female VNO via the production of Ins(1,4,5)P 3 . This result complements other studies that show Ins(1,4,5)P 3 levels increase in the VNO membrane preparations during stimulation with urinary pheromones (Sasaki et al, 1999;Kroner et al, 1996;Wekesa and Anholt, 1997;Wekesa et al, 2003;Inamura et al, 1997a;Inamura et al, 1997b). The role of Ins(1,4,5)P 3 in the production of calcium and generation of an action potential is still uncertain along with the role of calcium once it has entered the cell.…”
Section: Discussionsupporting
confidence: 85%
“…There is considerable evidence indicating that some odorants do not induce an increase in cAMP but rather the concentration of inositol, 1, 4, 5-triphosphate (InsP3) is increased [1,10]. InsP3 formation can increase intracellular Ca 2+ [11] and activate Ca 2+ -dependent K + channels or Ca 2+ -dependent non-specific cation channels [1,[12][13], which in turn generate receptor potential and depolarize the olfactory neuron, thus providing a signal for further neuronal processing. In addition to cAMP and InsP3, diverse olfactory transduction pathways, such as the activation of cAMP/cGMP-gated channels [14] reported a fast ionotrophic response and found no evidence of the involvement of G-protein or cAMP, cGMP or InsP3 while Wicher et al [20] showed that insect ORs induce the synthesis of cAMP through a G-protein that in turn activates Or83b, which serves as a cAMP-gated ion channel.…”
mentioning
confidence: 99%
“…They found that the Gα o mutant male mice are less aggressive, and the maternal aggression in females is also severely reduced [13]. Studies have shown that vomeronasal transduction involves release of IP 3 [16][17][18][19]. In the garter snake, a chemo attractant isolated from its prey induced the generation of inositol-1,4,5-trisphosphate in the VNO [18].…”
mentioning
confidence: 99%
“…In the garter snake, a chemo attractant isolated from its prey induced the generation of inositol-1,4,5-trisphosphate in the VNO [18]. It has been shown that dialysis of IP 3 into the turtle and rat VNO induces inward currents [17]. The female porcine and mouse VNO can be stimulated by chemosensory cues to cause an increase of IP 3 [16,19].…”
mentioning
confidence: 99%
See 1 more Smart Citation